A Comparison of Early Childhood Preservice Teachers' Beliefs about Music and Developmentally Appropriate Practice between South Korea and the US. Issue 2 (June 2013) - Kim, Hae Kyoung
THE PURPOSE OF THIS study is to examine the beliefs of early childhood preservice teachers in Korea (South) and the US about music, developmentally appropriate practices (DAP), and the relationship between the two. Participants of the study generally believed in the importance of music. In terms of the benefits of music, teachers believed more in the aesthetic and social-emotional benefits of music than quality-of-life benefits for young children. The results indicate that preservice teachers in Korea possess stronger beliefs about the importance of music than the teachers in the US. In particular, preservice teachers in Korea hold stronger beliefs about aesthetic benefits of music than their US counterparts. All the teachers in the study generally endorsed DAP, yet Korean preservice teachers had stronger beliefs in DAP. In this examination of the relationship between music and DAP, prospective teachers in Korea demonstrated more positive acceptance of the relationship. Some differences were found in the correlations of subcategories of music and DAP between the teachers in the US and Korea. This study may influence the design and implementation of teacher education programs in Korea and the US with regard to not only music curricula but other subjects as well. Discussions and implications for early childhood teacher educators are provided.